Using team rewards and individual assessment to incentivize collaboration in team projects - JONGJAROENKAMOL, Prasart (Institutional Knowledge at Singapore Management University, 2023)
Team projects are commonly used in higher education across different disciplines to promote cooperation among students. However, achieving this objective can be challenging. To address this issue, educators have explored various strategies, such as implementing peer evaluation or having periodic consultations with teams. In this paper, I present a novel approach to team assessment that combines team rewards with individual assessment. In this assessment, each team member independently takes a quiz, and the team's score is determined by the average performance of its members. Consequently, the team reward becomes intricately tied to the individual learning outcomes of all team members. This study offers an exemplary implementation of the proposed assessment scheme within an undergraduate management accounting class and reports students’ perceptions of this assessment approach.